Hot Topics in Endocrine and Endocrine-Related Diseases - Fedele, Monica (IntechOpen, 2013)
This book covers a selected number of hot topics in endocrine and hormone-related pathologies, discussed by eminent scientists and clinicians coming from different countries of the world. It deals with advanced recent trends in the field, including neuroendocrine and pituitary tumors, thyroid dysfunctions, diabetes and a series of endocrine-related diseases, such as those related to the anabolic effects of testosterone, obesity, cancer, the liver complications of diabetes and the pediatric nonalcoholic fatty liver disease. The readers should be able to have a basic, as well as critic and advanced, overview of these selected hot pathologies of the endocrine system.